Cerrado´s prehistory: Cerrado´s prehistory (Élisée - Revista de Geografia da UEG, 2020)
The present work aims at presenting the Cerrado’s Biogeographic System which, due to the environmental diversity, to the variety of resources and to the possibilities of subsistence, has had, since the end of the Pleistocene, fundamental importance in the fixation of human populations in the central areas of Brazil. Beyond the analysis concerning the system’s formation, this paper presents the importance of the relationship established by groups of hunters and gatherers with this type of environment is highlighted, a very wise relationship, that created a unique cultural processes. In this study, it is also verified that most of the characteristics of this relationship are highlighted in the culture of horticultural groups. In the end, it is concluded that it is fundamental to protect the environment, the culture and the history of the region, in order to better understand the function of this system for native populations, seeking legal mechanisms for the preservation of this heritage, both in its physical and cultural aspects. Keywords: Cerrado´s Prehistory. Cerrado. Anthropology.
Keywords: Keywords: Cerrado´s Prehistory. Cerrado. Anthropology.